2017
DOI: 10.1007/s10792-017-0654-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive phase and its association with surgical outcomes in Baerveldt implantation

Abstract: Baerveldt implantation is an effective procedure with high success rate. HP was common after Baerveldt implantation. Preoperative IOP and numbers of previous glaucoma surgery are risk factors for developing HP. Presence of HP can predict whether long-term anti-glaucoma medication(s) are needed or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
1
1
2
Order By: Relevance
“…Regarding previous surgeries, particularly cataract surgery, we found that pseudophakic and aphakic eyes were less likely to develop HP. This finding contrasts with previous results, such as the studies by Chansangpetch et al ,[ 12 ] Duch et al ,[ 13 ] and Dubey et al . [ 5 ]…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Regarding previous surgeries, particularly cataract surgery, we found that pseudophakic and aphakic eyes were less likely to develop HP. This finding contrasts with previous results, such as the studies by Chansangpetch et al ,[ 12 ] Duch et al ,[ 13 ] and Dubey et al . [ 5 ]…”
Section: Discussioncontrasting
confidence: 99%
“…4 ]. Similar findings are reported in eyes with BGI by Chansangpetch et al ,[ 12 ] which supports that HP could represent a form of early surgical failure and not a “phase,” as previously proposed by Nouri-Mahdavi and Caprioli. [ 3 ]…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may start after 10 days of surgery and persist up to 6 months requiring AGM for control of IOP. The subsequent reduction in bleb height, with step-down of AGM, or discontinuation, was defined as resolving or resolved HTP [ 14 ].…”
Section: Introductionmentioning
confidence: 99%